Pengelolaan Kelas Pendidikan Anak Usia Dini: Kajian Kepemimpinan - kurniawan, diki; Karim, Abdul (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2024)
Educators are the most important element in effective and efficient classroom management. So we need an educator who has a leadership style that encourages students to increase their potential. Apart from that, developing aspects of student development such as aspects of moral and religious values, cognitive aspects, language aspects, physical motoric aspects, and social emotional aspects. This research aims to determine the extent of the leadership style possessed by early childhood educators in managing the classroom. Data collection used an online survey with 79 respondents spread across 3 provinces, namely Papua province, South Papua province and Central Papua province. The results of the research are that educators are more inclined to apply a participative leadership style by 61%. Followed by a visionary style of 59% and a situational style of 58%. Meanwhile, authoritarian leadership style was 19%.